Open cell geopolymer foams by a novel saponification/peroxide/gelcasting combined route - Cilla, Marcelo Strozi; Morelli, Márcio Raymundo; Colombo, Paolo (Journal of the European Ceramic Society, 2014)
Using a novel saponification/peroxide/gelcasting combined route it was possible to produce geopolymer foams with a total porosity of ∼85vol%, open porosity as high as ∼70vol%, average cell size (D50) of 318μm, and possessing a specific surface area of 50m2/g. The in situ formation of surfactants by the saponification reaction of oil in the geopolymer alkaline environment led to increased total and open porosity in comparison to alternative methods for the fabrication of geopolymer foams.